Effects of Resistance Training Prior to Total Hip or Knee Replacement on Post-operative Recovery in Functional Performance: A Systematic Review and Meta-Analysis - Jørgensen, Stian Langgård; Kierkegaard, Signe; Bohn, Marie Bagger; Aagaard, Per; Mechlenburg, Inger (Frontiers in Sports and Active Living, 2022)
Objective To evaluate the effectiveness of pre-operative resistance training in patients allocated to TJR surgery on selected post-operative outcomes, via a meta-analysis of studies using exercise modalities and loading intensities objectively known to promote gains in muscle size and strength in adults of young-to-old age. Design A systematic review and meta-analysis. Literature Search Cochrane Central, MEDLINE, EMBASE, and PEDro were searched on August 4th 2021. Study Selection Randomized Controlled Trials (RCTs) were included if (i) they compared pre-operative lower-limb-exercises before elective TJR with standard care, (ii) explicitly reported the exercise intensity, and (iii) reported data on functional performance. Data Synthesis This systematic review and meta-analysis is reported in accordance with the PRISMA reporting guidelines. A random effects model with an adjustment to the confidence interval was performed for pooling the data. Results One thousand studies were identified. After applying exclusion criteria, five RCTs were located including 256 participants (mean age ranged from 61 to 72 years, 54% women). Moderate-to-large improvements in functional performance and maximal knee extensor strength were observed at 3 months after surgery along with small-to-moderate effects 12 months post-operatively. For patient-reported outcomes, small-to-moderate improvements were observed at 3 months post-operatively with no-to-small improvements at 12 months. Conclusion Prehabilitation efforts involving progressive resistance training provides an effective means to improve post-operative outcomes related to functional performance, knee extensor strength and patient-reported outcome in patients undergoing TJR. Due to large methodological diversity between studies, an optimal loading intensity remains unknown. Systematic Review Registration Prospero ID: CRD42021264796.